Investigation of time dependent heat and mass transportation for drying of 3D porous moist objects in convective conditions - Selimefendigil, Fatih; Coban, Seda Ozcan; Öztop, Hakan Fehmi (Elsevier France-Editions Scientifiques Medicales Elsevier, 2021)
Three-dimensional numerical study of convective drying process was investigated for two porous moist blocks in a channel under turbulent flow conditions by considering different parameters which are effective on heat and moisture transfer phenomena. The 3D unsteady flow and heat and mass transfer equations were solved with Galerkin weighted residual finite element method. Drying objects were rectangular shaped porous objects and effects of size and distance between the objects, velocity and temperature of inlet drying air were investigated with varying values. Transport of heat and moisture for the problem was evaluated. Obtained results showed that all of the changing parameters had significant effects on flow properties, heat and mass transfer phenomena in 3D. As the interspacing between the blocks increases, it has a positive impact on the drying process especially for second porous block even though it is not as effective as the velocity or the size. As the height of the porous block increases, due to the blockage effect it has adverse effects on the transportation phenomena.
Keywords: Convective drying; Heat and mass transfer; Moist object; Porous medium; Finite element method